Pediatric Fahr Syndrome Secondary to Hypoparathyroidism with Paraparesis-Like Presentation: A Rare Case from West Borneo: Pediatric Fahr Syndrome with Paraparesis-Like Presentation - Anna Marita Gelgel; Renald Patria Dharmansyah; Melda Melda; Pascanus Lamsihar Parluhutan Togatorop; Anthony Ekaputra (Universitas Airlangga, 2026)
Highlight: A paraparesis-like presentation in pediatric Fahr syndrome is uncommon. Paraparesis-like symptoms were associated with basal ganglia involvement and hypocalcemia. Calcitriol is preferred over cholecalciferol in hypoparathyroidism. ABSTRACT Introduction: Pediatric Fahr syndrome is a rare disorder with diverse clinical manifestations, making its diagnosis challenging. In West Borneo, access to advanced diagnostic facilities is limited, increasing the risk of misdiagnosis and delayed treatment. To our knowledge, no previous cases have described hypoparathyroidism–associated Fahr syndrome in a child presenting with a paraparesis-like gait disturbance. Case: We report a rare case of a 9-year-old girl with generalized tonic-clonic seizures without fever, accompanied by bilateral lower-limb weakness. She had a history of recurrent seizures several months before presentation. Neurological findings showed a flaccid, paraparesis-like gait disturbance of the lower limbs. Laboratory evaluation revealed hypocalcemia and reduced parathyroid hormone levels. CT imaging revealed symmetrical calcification of the basal ganglia and subcortical white matter. A working diagnosis of Fahr syndrome Secondary to hypoparathyroidism was made. Although hypocalcemia was corrected and seizure control was initially achieved, the patient experienced recurrent seizures and eventually died due to pneumonia. Conclusion: Fahr syndrome in children may mimic paraparesis but often presents with gait disturbances caused by basal ganglia calcifications. Secondary causes, especially hypoparathyroidism, should always be considered during the diagnostic evaluation. As history-taking and physical examination alone may be insufficient to exclude other differential diagnoses, additional laboratory and imaging investigations are required. When the underlying cause remains uncertain, symptomatic management and parental counseling should be initiated while the patient awaits referral to a higher-level healthcare facility.